Dielectric properties of coals in the low-terahertz frequency region. (15th December 2015) - Fan, Wei; Jia, Chengyan; Hu, Wei; Yang, Chuanfa; Liu, Lingyu; Zhang, Xiansheng; Chang, Tianying; Cui, Hong-Liang
Abstract: The dielectric properties of Shanxi anthracite and Shandong bituminous coals in China are investigated in the low-terahertz (THz), W-band of frequency from 75 GHz to 110 GHz for the first time. In this frequency range, the complex dielectric constant of coal samples is obtained using the free space method. It is found that both the real parts of the dielectric constant for bituminous and anthracite decrease considerably with increasing frequency from 75 GHz to 110 GHz. The anthracite coals exhibit higher real and imaginary part values than bituminous coals. The imaginary part of the coal samples exhibits a more significantly decreasing trend in the frequency range from 90 GHz to 110 GHz compared with frequencies below 90 GHz. The dielectric properties of all the coal samples are strongly dependent on the moisture content of the coals. Increasing moisture content leads to higher complex dielectric constant values. The effect of moisture on the dielectric properties of coals depends substantially on the influence of moisture content on the transmission and reflection of THz wave in the coals. The results show that the transmission coefficient of anthracite and bituminous exhibits an exponentially decreasing trend with increasing moisture content (from 0% to 10%). However, the reflection coefficient seems to follow a Gaussian-like changing trend with increasing moisture content, reaching a maximum around 4.5%.